Leitura do texto escrito no ensino de Matemática: Compreensão textual na interação professor-aluno - Soares, Izidio Silva (2018)
This research analyzes the reading made by Mathematics teacher to deal wit h the content Divisibility in a class of the 6° Year of Elementary School in a public school, observing textual comprehension strategies built in the interaction between teacher-students / student- teacher / student- through questions / answers. The research inserts a qualitative field approach with observation, records of the Mathematics classes and questionnaire application. The data were generated through the observations and class recordings regarding the content Divisibility, in which the teacher made her presentation based on reading the written text of Mathematics. The theoretical assumptions of Mathematics Education, Reading and Mathematical Language guided the analysis of the corpus of this research, verifying how the reading used by the Mathematics teacher in explaining the content Divisibility interfered in the students' participation in this content by the students, also, they are faced with understanding mathematical language. The discussion reveals the importance of working with reading in Mathematics classes, fundamentally necessary for the formation of the student reader, since the teacher of this discipline is also a reader trainer. The study allows recommendations regarding the reading used in the classroom to understand the Mathematical language referring to the content Divisibility, in which students tend to participate in class by expressing their mathematical reasoning, especially through the language spoken among students to deal with content in the classroom.